Comparison of magnetic resonance spectroscopy (MRS) with arterial spin labeling (ASL) in the differentiation between mitochondrial encephalomyopathy, lactic Acidosis, plus stroke-like episodes (MELAS) and acute ischemic stroke (AIS). (September 2018) - Li, Xiaodi; Wang, Yuzhou; Wang, Zhanhang; Lu, Jianjun; Xu, Yan; Ye, Jinlong; Kuang, Zuying; Li, Bo; Pan, Mengqiu; Chen, Wenming; Lu, Shuisheng; Zhou, Ziyang; et al.
Highlights: Presenting as stroke mimics, MELAS can hardly be diagnosed without delay in the absence of advanced neuroimaging evaluations. Lactate peak detected from the stroke-like lesion could not differentiate MELAS from acute ischemic stroke. Arterial spin labeling has high sensitivity and specificity in rapid identification of MELAS from acute ischemic stroke. Abstract: To compare the utility and limitation of magnetic resonance spectroscopy (MRS) and arterial spin labeling (ASL) in the differentiation between mitochondrial encephalomyopathy, lactic acidosis, plus stroke-like episodes (MELAS) and acute ischemic stroke (AIS), a retrospective review of 17 MELAS and 26 AIS patients were performed. In all patients both MRS and ASL scans were performed within 1 week after admission. Demographic, clinical, laboratory and MR imaging data were reviewed and compared between the two groups. Compared with AIS, MELAS patients had a younger age of onset, a longer disease duration, a higher occurrence of epilepsy attack, occipital and parietal lesions, and dilated cerebral arteries (P < 0.05). In all MELAS patients lactate peak and hyperperfusion of the lesion was revealed. However in AIS lactate peak was observed in only 69.2% and hyperperfusion was observed in only 34.6% ischemic lesions (P < 0.05). Choline/Creatine ratios and Lactate/Creatine ratios were higher in AIS, while in MELAS cerebral blood flow and lesion-normal perfusion ratio was much higher (P < 0.05). No correlations was found between metabolite ratios and perfusion parameters in either group (P > 0.05). Area under curve (AUC) of perfusion for the differentiation between MELAS and AIS was 0.958 (P < 0.001). The cut-off value was 2.075, with a sensitivity of 88.2% and a specificity of 96.2%. AUC of Lactate/Creatine ratio was 0.469 (P = 0.737). Utility of MRS is limited in the differentiation between MELAS and AIS, while MR perfusion profiles are much more sensitive and specific.